Impact of Nigella Sativa on Weight of Testis & Body Weight in Doxorubicin Treated Albino Rats (Medical Forum Monthly, 2022)
Objective: To measure impact of nigella sativa (NS) on weight of testis & body weight and doxorubicin treated albino rats.Study Design: Experimental workPlace and Duration of Study: This study was conducted at the BMSI animal House, Karachi from 1st March 2017 to 4 April 2017 (total 35 days).Materials and Methods: Experimental work was take place on 40 animals of 16 weeks old in the animal house for 35 days. Animals were separated into 4 sets, A1, B2, C3 & D4. A1 served as control, B2 receive Doxorubicin 3 mg/kg /7 days intraperitonealy, C3 receive Nigella sativa 1000mg/kg everyday orally along with Doxorubicin 3 mg / kg /7 days intraperitonealy and D4 receive extract of Nigella sativa 1000mg/kg everyday orally. After completion of experiment, animals were sacrifice and tissue material were well-preserved for staining.Results: In B2 body weight was noticeably reduced, bute amended in C3 which were given Nigella sativa along with Doxorubicin.Conclusion: This study reveals that Nigella sativa amended the weight reduction.